The main directions of state regulation of a small and middle entrepreneurship in the modern economy - A. Z. Gusov; A. A. Baitursunov (Путеводитель предпринимателя, 2020)
The article discusses the place and role of small and medium entrepreneurship in the modern economy as economic activity that provides the solution to fundamental economic and social problems. In this regard, the conclusion about the necessity of state support of development of small and medium enterprises and reveals the basic directions of state policy in the field of entrepreneurship.